DETERMINANTS OF FINANCIAL REPORT PUBLICATION ON REGIONAL GOVERNMENT WEBSITES IN CENTRAL SULAWESI - Ayu Kumala Dewi; Muhammad Din; Nina Yusnita Yamin; Masruddin Masruddin (JAT : Journal Of Accounting and Tax, 2026)
The goal of this study is to examine how the posting of financial data on regional government websites in Central Sulawesi Province is impacted by political competitiveness, government spending, local government size, audit opinions, and local wealth. This study uses a quantitative methodology and includes all of Central Sulawesi Province's regencies and cities for the years 2022–2024. The study population consists of 12 regencies and 1 city, for a total of 39 observations. The Central Sulawesi Province's regencies and cities' websites, local revenue and spending budget documents, and yearly financial reports were the sources of the data. In this instance, the data was analyzed using WarpPLS 8.0 software and the Partial Least Squares with Structural Equation Modelling (PLS-SEM) approach. The study's findings indicate that the publication of financial reports on regional government websites is positively and significantly impacted by government spending, local government size, and audit views, but not by political competitiveness or local wealth. This study demonstrates that regional governance quality and financial management skills have a greater impact on the release of financial reports online than do regional fiscal capacity and political considerations.